Analisis kemampuan siswa dalam menyelesaikan soal High order thinking skill (hots) pada materi Aritmatika sosial berdasarkan Gaya Belajar Siswa - Maria; Zaki M; Amalia R (Universitas Samudra, 2021)
The purpose of this study was to analyze the ability of students to solve HOTS questions on social arithmetic materials based on student learning styles such as auditory, visual and kinesthetic learning styles. Descriptive research method with a qualitative approach. This research was conducted at MTs Dewantara. The subjects of this study were 6 grade VIII students of MTs Dewantara. The results showed that the ability of subjects with auditory learning styles was able to solve items with type C4 (Analysis), C5 (Evaluation) and C6 (Creating). Subjects with a Visual learning style were able to solve items with type C4, but for items with type C5 and C6, subjects were unable to complete. Subjects with the Kinesthetic learning style were able to solve items with type C4, but were unable to solve items with types C5 and C6.